Voluntary exercise prior to traumatic brain injury alters miRNA expression in the injured mouse cerebral cortex - W. Miao; T.H. Bao; J.H. Han; M. Yin; Y. Yan; W.W. Wang; Y.H. Zhu (Brazilian Journal of Medical and Biological Research, 2015)
MicroRNAs (miRNAs) may be important mediators of the profound molecular and cellular changes that occur after traumatic brain injury (TBI). However, the changes and possible roles of miRNAs induced by voluntary exercise prior to TBI are still not known. In this report, the microarray method was used to demonstrate alterations in miRNA expression levels in the cerebral cortex of TBI mice that were pretrained on a running wheel (RW). Voluntary RW exercise prior to TBI: i) significantly decreased the mortality rate and improved the recovery of the righting reflex in TBI mice, and ii) differentially changed the levels of several miRNAs, upregulating some and downregulating others. Furthermore, we revealed global upregulation of miR-21, miR-92a, and miR-874 and downregulation of miR-138, let-7c, and miR-124 expression among the sham-non-runner, TBI-non-runner, and TBI-runner groups. Quantitative reverse transcription polymerase chain reaction data (RT-qPCR) indicated good consistency with the microarray results. Our microarray-based analysis of miRNA expression in mice cerebral cortex after TBI revealed that some miRNAs such as miR-21, miR-92a, miR-874, miR-138, let-7c, and miR-124 could be involved in the prevention and protection afforded by voluntary exercise in a TBI model.